Remote working and occupational stress: Effects on IT-enabled industry employees in Hyderabad Metro, India - Prasad, K.D.V.; Vaidya, Rajesh; Rani, Ridhi (Frontiers in Psychology, 2023)
In the present study, the researchers reported the results of an empirical study on remote working and occupational stress and their effects on employees’ job satisfaction, motivation, and performance. Remote working has three subscales: self-proficiency, technology, and teamwork. Intrinsic and extrinsic motivation subscales were included to assess employee motivation. A simple random sampling method was used to select the subjects who are employees of the IT-enabled industries in Hyderabad Metro. A total of 513 responses were obtained on the remote working subscales—the effect on the independent variables, namely, employee self-proficiency, technology, teamwork, and occupational stress, on the dependent variables, namely, job satisfaction, intrinsic motivation, extrinsic motivation, and performance. The measured Cronbach’s alpha was in the range of 0.64–0.77, other reliability statistics split-half (odd-even) correlation was in the range of 0.62–0.84, and theSpearman–Brown prophecy was in the range of 0.70–0.91, demonstrating the reliability and internal consistency of the research instrument. The general linear model results indicated that all the independent variables, namely, self-proficiency, teamwork, and Occupational stress, are statistically significant and influence the outcome variables. The general linear model results also indicated statistically significant age differences in the dependent variables; however, there were no statistically significant gender differences. Of the independent variables, self-proficiency influences job satisfaction, intrinsic motivation, and performance (p < 0.01); teamwork influences employee job satisfaction and extrinsic motivation (p < 0.01 and p < 0.05); and Occupational stress influences performance (p < 0.01), which are statistically significant and thus influence the outcome variables. The model predicted a statistically significant influence of age (p < 0.01) on all the dependent factors, namely, job satisfaction, intrinsic motivation, extrinsic motivation, and performance. The study revealed that remote working is one of the major factors causing anxiety and employee stress. The main reasons are the absence of interaction with peers, the absence of routine fun during breaks, and work–family conflicts. Another observation is that the absence of peer–employee interaction demotivates the employees as there is no competition among the employees during remote working. The authors recommend that organizations develop an integrated human resource policy and performance management system that addresses the issues of employee stress, remote working concerns, peer–employee interactions, and pandemic-type situations. As there are several factors such as occupational stress, job satisfaction, motivation, peer interactions, and remote working concerns, employee stress-coping strategies affect the performance of an employee. The multiple mediation analysis indicates no statistically significant influence of the mediator variables, i.e., occupational stress and job satisfaction, on performance through remote working.